Keseimbangan produksi dan konsumsi dalam islam dan ekonomi modern: upaya mewujudkan kehidupan ekonomi yang adil, berkelanjutan, dan berbasis nilai etika - Ummah, Fina Zaimatul (Maliki Interdisciplinary Journal, 2025)
This article examines the concept of balancing production and consumption in the perspective of Islam and modern economics. The research aims to analyze the Islamic view of needs and wants, identify the challenges of overconsumption in the contemporary era, and formulate strategies for the implementation of Islamic economic principles that are just and sustainable. Using a literature review approach, this article finds that Islam emphasizes the principles of tawazun (balance), prohibition of israf (excess), and social responsibility in economic activities. The main challenges faced include the culture of consumerism, the influence of digital technology, and dependence on conventional financial systems. Solutions offered include the integration of sharia values in economic policy, strengthening Islamic consumption education, developing halal products, and the active role of consumers in implementing a simple lifestyle. The research findings show that Islamic values are not only relevant for creating an ethical economic system, but are also able to answer modern challenges with a holistic approach that integrates material and spiritual aspects. This article recommends multi-stakeholder collaboration to realize economic practices that are aligned with Islamic principles, so as to achieve sustainable shared prosperity.